THE INFLUENCE OF INCENTIVES, WORK ENVIRONMENT, AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE IN THE BOOK PUBLISHING INDUSTRY IN THE CITY OF MAKASSAR - Chakti, Andi Gunawan Ratu (Indonesian Journal Of Economy Studies, 2023)
This research aims to explore, analyze, and interpret the impact of incentives, work environment, and leadership style on employee performance in the book publishing industry in the city of Makassar. The research approach used is quantitative descriptive, with a population and sample consisting of 31 employees in the book publishing industry in the city of Makassar. Data collection is done through interviews, questionnaires, and literature studies. The obtained data will be analyzed using statistical tools and SPSS version 24 software.The results of the study indicate that:Incentives have a positive and significant impact on the performance of employees in the book publishing industry in the city of Makassar. Overall, incentives have a strong influence on improving employee performance, which is a crucial factor in achieving organizational goals.The work environment also has a positive and significant impact on the performance of employees in the book publishing industry in the city of Makassar. Leadership style is an important factor that supports employees in developing their potential optimally to contribute to the organization's goals with full awareness.Leadership style also has a positive and significant impact on performance in the book publishing industry in the city of Makassar. Key factors in incentives include the atmosphere and supporting facilities that play a crucial role in the implementation of job tasks for employees in the book publishing industry in the city of Makassar.